2014
DOI: 10.1088/0004-637x/783/2/122
|View full text |Cite
|
Sign up to set email alerts
|

The Allwise Motion Survey and the Quest for Cold Subdwarfs

Abstract: The AllWISE processing pipeline has measured motions for all objects detected on Wide-field Infrared Survey Explorer (WISE) images taken between 2010 January and 2011 February. In this paper, we discuss new capabilities made to the software pipeline in order to make motion measurements possible, and we characterize the resulting data products for use by future researchers. Using a stringent set of selection criteria, we find 22,445 objects that have significant AllWISE motions, of which 3525 have motions that … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
217
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(230 citation statements)
references
References 93 publications
12
217
1
Order By: Relevance
“…We started by analyzing bright sources in the new catalogs of high proper motion sources by and Kirkpatrick et al (2014). We selected the brightest sources with the highest proper motion that were visible in April from the southern skies (i.e.…”
Section: Sample Selection and Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…We started by analyzing bright sources in the new catalogs of high proper motion sources by and Kirkpatrick et al (2014). We selected the brightest sources with the highest proper motion that were visible in April from the southern skies (i.e.…”
Section: Sample Selection and Observationsmentioning
confidence: 99%
“…Later, the multiepoch nature of the WISE mission provided proper motions for over twenty thousand individual sources Kirkpatrick et al 2014), including the discoveries of the third and fourth closest systems to the Sun (Luhman 2013. These are the closest binary BD, and the coldest BD known.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have found clear evidence for dynamically cold (slow-moving) and hot (fast-moving) populations of ultracool dwarfs that are consistent with thin disk and thick disk/halo populations (e.g., Faherty et al 2009;Schmidt et al 2010;Dupuy & Liu 2012), implying that ultracool dwarfs form in the same manner as hotter stars. Searches for high proper motion objects, often using surveys with shorter time baselines, have identified rare, fast-moving objects that are typically members of the older, low-metallicity populations (e.g., Jameson et al 2008;Kirkpatrick et al 2014;Smith et al 2014b) or very nearby, previously overlooked objects (e.g., Luhman 2014; Luhman & Sheppard 2014;Kirkpatrick et al 2016;Schneider et al 2016a). Proper motions measured from the large surveys have enabled us to identify the substellar members of nearby young moving groups (e.g., Gagné et al 2015cGagné et al , 2015bFaherty et al 2016;Liu et al 2016), a population crucial to our understanding of brown dwarf evolution over their first few hundred million years.…”
Section: Introductionmentioning
confidence: 99%
“…ultracool subdwarfs contains approximately 50 objects, in particular 11 L-type subdwarfs (Burgasser et al 2003a;Burgasser 2004;Cushing et al 2009;Sivarani et al 2009;Lodieu et al 2010Lodieu et al , 2012Kirkpatrick et al 2010Kirkpatrick et al , 2014. Because M subdwarfs are old components of our Galaxy (a few Gyr) with effective temperatures in the 3000-4000 K range (Rajpurohit et al 2014) we do not expect to detect lithium in absorption in their optical spectra because all the Li has been burnt.…”
Section: Introductionmentioning
confidence: 97%